Rhizosphere Microbiome: The Emerging Barrier in Plant-Pathogen Interactions - Li, Jingtao; Wang, Chenyang; Liang, Wenxing; Liu, Sihui (Frontiers in Microbiology, 2021)
In the ecosystem, microbiome is widely existing in soil, animals and plants. With the rapid development of computational biology, sequencing technology and omics analysis, the important role of soil beneficial microbial community is being revealed. In this review, we mainly summarized the roles of rhizosphere microbiome, revealing its complex and pervasive nature contributing to the largely invisible interaction with plants. The manipulated beneficial microorganisms function as an indirect layer of the plant immune system by acting as a barrier to pathogen invasion or inducing plant systemic resistance. Specifically, plant could change and recruit beneficial microbial communities through root-type-specific metabolic properties, and positively shape their rhizosphere microorganisms in response to pathogen invasion. Meanwhile, plants and beneficial microbes exhibit the abilities to avoid excessive immune responses for their reciprocal symbiosis. Substantial evidences show pathogens might utilize secreting proteins/effectors to overcome the emerging peripheral barrier for their advantage in turn. Overall, beneficial microbial communities in rhizosphere are involved in plant-pathogen interactions, and its power and potential are being explored and explained with the aim to effectively increasing plant growth and productivity.